2011
DOI: 10.1186/1756-0500-4-392
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for qPCR in hairy root cultures of peanut

Abstract: BackgroundHairy root cultures produced via Agrobacterium rhizogenes-mediated transformation have emerged as practical biological models to elucidate the biosynthesis of specialized metabolites. To effectively understand the expression patterns of the genes involved in the metabolic pathways of these compounds, reference genes need to be systematically validated under specific experimental conditions as established by the MIQE (Minimum Information for Publication of Quantitative Real-Time PCR Experiments) guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…Similarly, two reference genes would be sufficient for the SR and PL treatments, four for the PR and CL treatments, and five for the HL treatment. In the practical application, three reference genes for the PR (V 3/4  = 0.1335) and HL (V 3/4  = 0.1480) treatments, and two for the CL treatment (V 2/3  = 0.1282) could also be accepted using a threshold value of 0.15 [14], [21], [33], [34].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, two reference genes would be sufficient for the SR and PL treatments, four for the PR and CL treatments, and five for the HL treatment. In the practical application, three reference genes for the PR (V 3/4  = 0.1335) and HL (V 3/4  = 0.1480) treatments, and two for the CL treatment (V 2/3  = 0.1282) could also be accepted using a threshold value of 0.15 [14], [21], [33], [34].…”
Section: Resultsmentioning
confidence: 99%
“…This method showed that the optimal number of reference genes was 8, as indicated by the lowest Acc.S.D. (0.092); however, the setting of such a large number of reference genes is not practical [44]. Considering that Acc.S.D.…”
Section: Discussionmentioning
confidence: 99%
“…A 96 h time course per elicitor treatment was conducted including the following time points: 0, 0.5, 1, 3, 6,9,12,15,18,21,24,30,36,40,48,72 Extraction and Analyses of Stilbenoids from the Culture Medium. Stilbenoids were extracted from the medium of NaOAc-, H 2 O 2 -, and MeJA-treated hairy roots as described before.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%